2017
DOI: 10.5194/acp-2017-1022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraining fossil fuel CO<sub>2</sub> emissions from urban area using OCO-2 observations of total column CO<sub>2</sub>

Abstract: Abstract. Expanding urban populations and the significant contribution of cities to global fossil-fuel CO 2 (CO 2ff ) emissions emphasize the necessity of achieving independent and accurate quantifications of the emissions from urban area. In this paper, we assess the utility of total column dry air CO 2 mole fraction (X CO2 ) data retrieved from NASA's Orbiting Carbon Observatory 2 (OCO-2) observations to quantify CO 2ff emissions from cities. Observing System Simulation Experiments (OSSEs) are implemented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…These limitations mostly inhibit a straightforward estimation of the emission strength of localized sources of CO 2 and CH 4 like cities, landfills, swamps or fracking and mining areas from satellite observations. Recently OCO-2 data were used for estimating the source strength of power plants (Nassar et al, 2017) and urban emissions (Ye et al, 2017). However, this can only be done for power plants and urban areas that lie directly under the OCO-2 overpass locations.…”
Section: Introductionmentioning
confidence: 99%
“…These limitations mostly inhibit a straightforward estimation of the emission strength of localized sources of CO 2 and CH 4 like cities, landfills, swamps or fracking and mining areas from satellite observations. Recently OCO-2 data were used for estimating the source strength of power plants (Nassar et al, 2017) and urban emissions (Ye et al, 2017). However, this can only be done for power plants and urban areas that lie directly under the OCO-2 overpass locations.…”
Section: Introductionmentioning
confidence: 99%
“…In complement to process-based inventories (Gurney et al, 2012), aircraft campaigns (Mays et al, 2009;Wecht et al, 2014), and analysis of satellite data Ye et al, 2017) among other methods, a common approach has been to deploy a network of sensors within and around a city (Breon et al, 2014;McKain et al, 2015McKain et al, , 2012Pugliese, 2017;Richardson et al, 2016;Shusterman et al, 2016;Verhulst et al, 2017). In complement to process-based inventories (Gurney et al, 2012), aircraft campaigns (Mays et al, 2009;Wecht et al, 2014), and analysis of satellite data Ye et al, 2017) among other methods, a common approach has been to deploy a network of sensors within and around a city (Breon et al, 2014;McKain et al, 2015McKain et al, , 2012Pugliese, 2017;Richardson et al, 2016;Shusterman et al, 2016;Verhulst et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen increased efforts to quantify greenhouse gas emissions at or below the scale of individual cities. In complement to process-based inventories (Gurney et al, 2012), aircraft campaigns (Mays et al, 2009;Wecht et al, 2014), and analysis of satellite data Ye et al, 2017) among other methods, a common approach has been to deploy a network of sensors within and around a city (Breon et al, 2014;McKain et al, 2015McKain et al, , 2012Pugliese, 2017;Richardson et al, 2016;Shusterman et al, 2016;Verhulst et al, 2017). The density and placement of sensors within a network, together with the local meteorology and the spatiotemporal pattern of emissions, determines the extent to which the network is reliably sensitive to emissions over the whole region of interest and within the relevant time scale.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent study indicated that the WRF‐VPRM was able to capture the atmospheric CO 2 temporal and spatial distributions and performed better than other global models in simulating diurnal variability of atmospheric CO 2 concentration field (Ahmadov et al, 2009). In the past decade, the application and evaluation of WRF‐VPRM mainly focused on North America (Feng et al, 2016; Hu et al, 2019b, 2020; Park et al, 2018; Ye et al, 2017) and Europe (Pillai et al, 2011). The model performances remain unknown in Asia including China due to the lack of observations, as well as model uncertainties due to uncertainties of VPRM parameters in the region (Dayalu et al, 2018; Hilton et al, 2013; Liu et al, 2015; Zhang et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Diao et al (2015) used WRF‐VPRM to investigate the spatiotemporal characteristics of NEE and surface CO 2 concentrations over the Yangtze River Delta region in China for 5 days, from 28 July to 2 August 2010. Ye et al (2017) assessed the biotic contribution to the XCO 2 enhancements during two short episodes (12–15 January and 1–4 August 2015) over the Pearl River Delta metropolitan region in China using the WRF‐VPRM. However, these short‐term (a few days) simulations could not reveal long‐term variations of CO 2 fluxes/concentrations.…”
Section: Introductionmentioning
confidence: 99%